Euskal literatura aldizkariak eta periferiak - Borda, Itxaro; Cano, Harkaitz; Sarasola , Beñat; Zabala, Juan Luis (EGAN, 2024)
MAHAI-INGURUA Itxaro Borda. Harkaitz Cano, Beñat Sarasola, Juan Luis Zabala